Eliminating Hepatitis C Virus Among Human Immunodeficiency Virus–Infected Men Who Have Sex With Men in Berlin: A Modeling Analysis. (12th July 2019) - Martin, Natasha K; Jansen, Klaus; an der Heiden, Matthias; Boesecke, Christoph; Boyd, Anders; Schewe, Knud; Baumgarten, Axel; Lutz, Thomas; Christensen, Stefan; Thielen, Alexander; Mauss, Stefan; Rockstroh, Jürgen K; et al.
Abstract: Background: Despite high hepatitis C virus (HCV) treatment rates, HCV incidence among human immunodeficiency virus (HIV)–infected men who have sex with men (HIV-infected MSM) in Germany rose before HCV direct-acting antivirals (DAAs). We model what intervention can achieve the World Health Organization (WHO) elimination target of an 80% reduction in HCV incidence by 2030 among HIV-infected MSM in Berlin. Methods: An HCV transmission model among HIV-diagnosed MSM was calibrated to Berlin (rising HCV incidence and high rates of HCV testing and treatment). We modeled the HCV incidence among HIV-diagnosed MSM in Berlin until 2030 (relative to 2015 WHO baseline) under scenarios of DAA scale-up with or without behavior change (among HIV-diagnosed MSM and/or all MSM). Results: Continuing current treatment rates will marginally reduce the HCV incidence among HIV-diagnosed MSM in Berlin by 2030. Scaling up DAA treatment rates, beginning in 2018, to 100% of newly diagnosed HCV infections within 3 months of diagnosis and 25% each year of previously diagnosed and untreated HCV infections could reduce the HCV incidence by 61% (95% confidence interval, 55.4%–66.7%) by 2030. The WHO target would likely be achieved by combining DAA scale-up with a 40% reduction in HCV transmission among HIV-diagnosed MSM and a 20% reduction among HIV-undiagnosed or HIV-uninfected MSM. Discussion: HCV elimination among HIV-infected MSM in Berlin likely requires combining DAA scale-up with moderately effective behavioral interventions to reduce risk among all MSM. Abstract : Dynamic modeling indicates that hepatitis C virus elimination among human immunodeficiency virus–infected men who have sex with men (MSM) in Berlin likely requires combining direct-acting antiviral scale-up with moderately effective behavioral interventions to reduce risk among all MSM.